Flecainide toxicity: a presentation to the emergency department with literature review. Issue 2 (28th February 2020) - Ghataoura, Rashpal; Patil, Shashank
Abstract : Flecainide toxicity can result in increased cardiovascular instability which can significantly alter patient outcome if not recognised early. In this case report, the management of a 68-year-old woman who took an unintentional overdose of flecainide is detailed. We look at the management she received in the emergency department and her successful recovery and follow-up since the admission. In addition, the case report outlines the ECG changes that are most commonly documented in flecainide overdose and reviews the frequently used treatment methods for the overdose as summarised in current literature.